2022
DOI: 10.21037/atm-22-475
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal miR-21 mediates HUVEC proliferation and migration through PTEN/PI3K/AKT in Crohn’s disease

Abstract: Background: Angiogenesis and vascular dysfunction play important roles in the occurrence and development of Crohn's disease (CD), but relevant mechanistic research is lacking. This paper aimed to use exosomal technology to elucidate the mechanism of vascular abnormalities in CD.Methods: Ultra-high-speed centrifugation was used to extract circulating exosomes. Electron microscopy, particle size, and biomarker detection were used for exome quality control. MicroRNA 21 (miR-21) levels were determined by quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Blood vessels are one of the largest and most important organs in the human body. We have found that exosomal miR-21 targeting Pten induced activation of the PI3K/AKT pathway and promoted migration and tube formation of human umbilical vein endothelial cells (HUVECs) in our previous study, which may be an important mechanism of abnormal angiogenesis in patients with CD (34). Therefore, we injected agomir-21, an exosomal miRNA analogue, into the tail vein of mice induced by TNBS and found that the miR-21 analogue could aggravate the manifestation of colitis in the model mice, while antagomir-21, an in vivo antagonist of miR-21, could alleviate these manifestations and effectively inhibit mesenteric angiogenesis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Blood vessels are one of the largest and most important organs in the human body. We have found that exosomal miR-21 targeting Pten induced activation of the PI3K/AKT pathway and promoted migration and tube formation of human umbilical vein endothelial cells (HUVECs) in our previous study, which may be an important mechanism of abnormal angiogenesis in patients with CD (34). Therefore, we injected agomir-21, an exosomal miRNA analogue, into the tail vein of mice induced by TNBS and found that the miR-21 analogue could aggravate the manifestation of colitis in the model mice, while antagomir-21, an in vivo antagonist of miR-21, could alleviate these manifestations and effectively inhibit mesenteric angiogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, miR-21 may play a positive regulatory role in angiogenesis. Our previous study found that the level of miR-21 in plasma exosomes of patients with active CD was elevated and the miR-21 can activate the PI3K/AKT pathway and promote the migration and tube formation of vascular endothelial cells by targeting inhibition of PTEN (34). We therefore hypothesized that the promoting effect of exosomal miR-21 on abnormal colonic vascular regeneration in CD model mice could be verified at the overall level so as to reveal a new vascular proliferation mechanism in the pathogenesis of CD, and that the therapeutic effect of antagomir-21, a specific miR-21 antagonist in vivo, on CD model mice could be preliminarily verified through the functional loss of miRNA in vivo, which could provide a further theoretical basis for the application of miRNA or miRNA antagonists in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVECs) of passages 3–5 used in this experiment were obtained from ScienCell (USA). After 24 ​h of coculture of PT scaffolds and BMSC/BMSC sheets, the supernatant was collected, named conditioned medium derived from BMSCs (BMSC-CM), and used to culture HUVECs to perform angiogenesis assays, such as wound healing and tube formation assays [ 36 ]. First, a wound healing assay was utilized to assess the migration capacity of HUVECs cultured in BMSC-CM.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to miR-125b-5p, miR-21-5p targets and inhibits TNFAIP3 [ 449 , 450 ]. Furthermore, miR-21 plays an oncogenic role by targeting FOXO1 [ 451 , 452 , 453 ] and PTEN [ 454 , 455 , 456 ], thereby activating the PI3K/AKT/mTORC1 pathway in DLBCL [ 350 ]. B-cell lymphoma/leukemia 11B ( BCL11B ) is another direct target of miR-21 [ 457 ].…”
Section: Exosomal Micrornas In the Pathogenesis Of Dlbclmentioning
confidence: 99%